Ecological restoration of mussel beds onto soft‐sediment using transplanted adults. Issue 3 (18th September 2017) - Wilcox, Mark; Kelly, Shane; Jeffs, Andrew
Abstract : The success of restoration initiatives to restore bivalve beds relies on sufficient recruitment of larvae to offset mortality of re‐established populations. Individuals of the nearly extirpated green‐lipped mussel are capable of surviving within the current environment of the Hauraki Gulf, New Zealand; however, it is uncertain what potential factors might inhibit the establishment and persistence of restored mussel beds. Four experimental mussel beds were established within a shallow soft‐sediment embayment and assessments of population dynamics were conducted approximately every 6 months over a 2‐year period. Deployed mussels quickly congregated into contiguous mussel beds that persisted throughout the study; however, only 26.2% of mussels that were initially established survived until the end of the study. The cause of this overall loss of mussels can be attributed to a near lack of observed recruitment, with only three individual recruiting mussels observed throughout the entire study. Despite similar mortality rates within the restored mussel beds to that of natural populations, these populations will be unsustainable long term given the lack of recruitment. Potential causes of the observed mortality and lack of recruitment are discussed, including environmental factors affecting non‐natal mussel stock and sea star predation. This research provides a foundation for the development of best‐practice methods in the restoration of green‐lipped mussels. However, further investigation into recruitment pathways and sources of mortality for adult mussels will be necessary to overcome the observed limitations if future restoration is to be successful.